Media Markets in the Focus of Social Network Analysis - Dovbysh, Olga (Journal of Economic Sociology, 2015)
This article presents a review of literature on the network structure of media markets. The focus on the network approach is not an accident: features which distinguish media markets from other markets as well as the specific nature of media products influence the network configurations and relations between actors in this market. The author explores how media markets are structured in terms of intra-market relations, what these relations are, and reasons for these relations and what network configuration is typical for media markets. This review focuses on the following questions: How is the media market organized in terms of the intramarket relations of its members? What relations exist in the market? What is the rationale of these relations? What configuration of the network is typical for the media market? The author suggests that the network structure of media markets can be explained by the peculiarities of media industries and media products. Thus, the literature review revealed that media markets can be characterized by a high share of informal relations within the market structure. Such structure allows reduced risks related to the impossibility of demand forecast for cultural goods and the dependency on individual tastes and fashion. The project-based work of many cultural products influences embedded links between actors. The power of personal social contacts is important, however it is not the same for different stages of the production chain for media products, or for different spatial scales of interrelations and in different sectors of media. In addition, informal relations are valuable for many types of activities — generating creative products, employment and career developing, etc. Structures of interlocking directorates also exist in media industries, however, there is no evidence that media companies are more intertwined than in other industries. Actors in cultural industries can be characterized by small world network configurations that enable more effective creative process, but can block the entrance of new participants and new ideas. A number of questions for further investigation are stated in the end of the article.